The local geographic origins of Russian-Jewish immigrants, circa 1900 - Joel Perlmann (Levy Economics Institute of Bard College, 2006)
This working paper concerns the local origins of Russian-Jewish immigrants to the United States, circa 1900. New evidence is drawn from a large random sample of Russian-Jewish immigrant arrivals in the United States. It provides information on origins not merely by large regions, or even by the provinces of the Pale of Settlement (where nearly all Russian Jews lived), some 25 in number; rather, most analysis is conducted in terms of some 230 districts that made up the administrative subdivisions of provinces. The sample evidence is coordinated with district-level data from the detailed publications of the 1897 Census of the Russian Empire. Finally, all of this evidence has been entered into digitized maps.
Keywords: J15; N30; N33; 330; Migration; economic history; economics of races